1960
DOI: 10.1039/tf9605600424
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and temperature dependence of diffusion coefficients for systems polymethyl acrylate and n-alkyl acetates

Abstract: Experimental data for the intrinsic diffusion coefficients 9 of methyl acetate, ethyl acetate, n-propyl acetate, and n-butyl acetate in polymethyl acrylate (P.M.A.) have been obtained as functions of penetrant concentration over a range of temperatures well above the glass transition point of pure P.M.A. For the four penetrants studied, plots of log 9 against ZQ are linear over the range of v1 at high temperatures and show downward curvature at low temperatures, where 7.11 is the volume fraction of penetrant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(134 citation statements)
references
References 7 publications
5
122
1
6
Order By: Relevance
“…One of the most promising and earliest free volume models was developed by Fujita. Fujita (Fujita et al, 1960;Fujita and Kishimoto, 1961) suggested the molecular transport to be due to a redistribution of free volume and not due to a thermal activation. The basic idea of this theory is that a diffusing molecule can only move from one position to another when, in its neighbourhood, the local free volume exceeds a certain critical value.…”
Section: Free Volume Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most promising and earliest free volume models was developed by Fujita. Fujita (Fujita et al, 1960;Fujita and Kishimoto, 1961) suggested the molecular transport to be due to a redistribution of free volume and not due to a thermal activation. The basic idea of this theory is that a diffusing molecule can only move from one position to another when, in its neighbourhood, the local free volume exceeds a certain critical value.…”
Section: Free Volume Theorymentioning
confidence: 99%
“…However, Fujita et al (1960) considered it inappropriate for the diffusion of small molecules like water in rubbery polymers, which is largely independent of the concentration. Kulkarni and Stern (1983) studied the diffusion of CO 2 , CH 4 , C 2 H 4 and C 3 H 8 in PE (φ a = 0.552) at 5°, 20°and 35°C for pressures reaching 4 MPa.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujita et al [19] have proposed a similar relationship from considerations based on the free volume theory.…”
Section: ¼ àDrc ð1þmentioning
confidence: 97%
“…The shape and size of a penetrant molecule will influence the rate of transport within the polymeric matrix. Some researchers have reported a decrease in diffusivity with an increase in the size of the penetrant [24][25][26]. The transport and diffusion in filled polymers depend on the nature of the filler, the degree of adhesion and their compatibility with the polymer matrix.…”
Section: Factors Contributing To the Transport Process Of Polymeric Nmentioning
confidence: 99%